2016
DOI: 10.1007/s11250-016-1159-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan

Abstract: A prospective study was conducted from November 2013 to February 2014 to estimate the spatial clustering; cumulative incidence and risk factors associated with avian influenza (AI) subtype H9 infection on commercial poultry farms of Pakistan. A total of 400 farms were enrolled and followed during the study period. Among these, 109 farms submitted samples suspected for AI to the laboratory, and only 47 farms were confirmed positive by hemagglutinin inhibition (HI) test. Data was collected from these 109 farms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The absence of footbath at the entrance of the shed or the absence of rubber boots for visitors can create a breach in biosecurity and increases the risk of infection. These factors were proven to be the deterrent of AI in the current study and also endorsed by other researchers (Woo & Park, 2008;Biswas et al, 2009;Abbas et al, 2012;Chaudhry et al, 2015;Chaudhry et al, 2017;Gompo et al, 2019). Three factors significantly enhanced seropositivity in the birds in the current the study.…”
Section: Discussionsupporting
confidence: 86%
“…The absence of footbath at the entrance of the shed or the absence of rubber boots for visitors can create a breach in biosecurity and increases the risk of infection. These factors were proven to be the deterrent of AI in the current study and also endorsed by other researchers (Woo & Park, 2008;Biswas et al, 2009;Abbas et al, 2012;Chaudhry et al, 2015;Chaudhry et al, 2017;Gompo et al, 2019). Three factors significantly enhanced seropositivity in the birds in the current the study.…”
Section: Discussionsupporting
confidence: 86%
“…In recent surveys in Vietnam, prevalence of the virus exceeded 3.5% in chickens in LBMs [61,62]; in various Chinese provinces prevalence was found to be upwards of 10% [63][64][65][66]. Several separate studies have shown that the prevalence in Bangladesh and Pakistan of H9 viruses in chickens at LBMs and farms was almost 10% [30,[67][68][69]. Another recent study has shown prevalence of upwards of 10% at LBMs in Egypt [70].…”
Section: Hyper-prevalence Of H9n2 Viruses In Poultrymentioning
confidence: 98%
“…In recent surveys in Vietnam, prevalence of the virus exceeded 3.5% in chickens in LBMs [71,72] and in various Chinese provinces, prevalence was found to be upwards of 10% [73,74,75,76]. Several separate studies have shown that the prevalence in Bangladesh and Pakistan of H9 viruses in chickens at LBMs and farms was almost 10% [35,77,78,79]. Another recent study has shown prevalence of upwards of 10% at LBMs in Egypt.…”
Section: History and Phylogeography Of H9n2 Virus In Poultrymentioning
confidence: 99%